The Relationship between Consumption of Frozen Food, Sweetened Soft Drinks, and Stress with The Nutritional Status of Adolescents - Bahar, Fajrin Nabatah; Lestari, Puji; Kurniasanti, Pradipta (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2023)
This study aims to determine the relationship between the consumption of frozen food, sweetened soft drinks, and stress and the nutritional status of adolescents at Pondok Pesantren Al-Hamid Cilangkap, East Jakarta. The method used is a cross-sectional design at the Al-Hamid Islamic Boarding School, Cilangkap, East Jakarta. The sample is 69 people. The data measured were frozen food consumption patterns, sweetened soft drinks using (FFQ) questionnaire, stress using (KPDS) questionnaire, and nutritional status measured using BMI—bivariate analysis using the Gamma test. The results of the study were respondents with a high frozen food consumption pattern (45%), high, moderate (17,4%), and low (37,6%), respondents with a consumption pattern of sweetened soft drinks (45%), high, moderate (17,4%) and low (37,6%). Respondents who experienced severe stress (45%), (17,4%) moderate stress, (7,3%) mild stress, (30,3%) no stress. The results of the bivariate test showed a relationship between consumption patterns of frozen food and nutritional status (p-value 0,000), a relationship between consumption patterns of sweetened soft drinks and nutritional status (p-value 0,000), and a relationship between stress and nutritional status (p-value 0.000). In conclusion, a significant relationship exists between consuming frozen food, sweetened soft drinks, and stress with nutritional status.